(untitled) (International Journal of Food and Nutritional Sciences, 2022)
People all over the world have had their perspectives and habits profoundly shaped by the advent of the Internet. Because of this boon, online retail has flourished, changing the shopping habits of regular people. Although Tumakuru residents are still getting used to it, online retailers have begun offering their wares to the city’s customers. In order to better understand online shopping habits, 180 residents of Tumakuru, Karnataka, are asked to fill out a survey created by the researchers themselves. The survey concludes that people prefer to shop online because it allows them to do so more quickly and provides access to a wider variety of products. Likes and dislikes are shared between sexes; both prefer home delivery and dislike not being able to physically handle the product. Cash on delivery is their preferred method of payment for clothing and accessories. Most buyers worry about their financial information being compromised, and their satisfaction with shopping online varies widely.